The Role of the University Professor in Advancing Society: The Arabic Language Teacher as a Model - Al-Nuaimi, Prof. Dr. Ammar Saadallah Reda Al-Nuaimi (Sulaimani Journal for Humanities, 2026)
Education has a significant impact on the advancement of nations. The Holy Qur'an has worked to achieve education with all its requirements, creating a generation immune to all the destructive influences on the individual and society that the nation will face in the future. This has already happened and continues to happen in every era of the nation's life. The modern world is witnessing rapid changes that are dissolving weak cultures. This is what they call "globalization" and the concepts related to this conflict that have subsequently become popular, such as the "clash of civilizations." The dangers of this newly emerging trend are well known; it is nothing but a type of war aimed at erasing the identity of the Islamic nation. It is well known that education has three pillars: the teacher, the curriculum, and the learner. The teacher is one of the most important of these pillars. The research was divided into two sections. The first was titled "The Positive Role of Teaching Arabic in Society," while the second was titled "Examples of Texts Directed at Instilling Lofty Values in Arabic Language Lessons.
Keywords: university professor; Renaissance; society; Arabic language